Perceptions of Teenage Consumers in Bukur Jiwan Toward Instagram-Based Product Advertising on @zuthe.hijab - Ilham Putri Andini; Asna Istya Marwantika; Sridar Samu (Niqosiya: Journal of Economics and Business Research, 2025)
Introduction: Consumer perception plays an essential role in marketing and building a positive image of a product. In the digital era, Instagram has become a widely used promotional medium, including by Zuthe Hijab, which actively advertises its products through the Instagram account @zuthe.hijab perceptions of advertising products on the Instagram account @zuthe.hijab in Bukur Jiwan Village, District Madiun. Research Methods: The research uses a qualitative descriptive approach with data collection techniques in the form of observation, in-depth interviews, and documentation. Six teenage women who are active on social media and live in the Bukur Jiwan village area were selected as informants in a purposive way. Results: Research results show that perception is influenced by internal factors such as needs, emotions, and personal experiences, as well as external factors like socio-sociocultural environment, popularity, and conditions in the social economy. Creative, varied, and interactive advertising​ can form perceptions and push consumers to purchase goods emotionally and rationally. Conclusion: Zuthe Hijab's Instagram marketing strategy effectively shapes positive perceptions among teenage consumers. Internal and external factors influence these perceptions and result in purchasing decisions based on individual socio-economic circumstances study are delivered.